Brief Report: Peripheral Monocyte/Macrophage Phenotypes Associated With the Evolution of Cognitive Performance in HIV-Infected Patients. (1st October 2017) - Fabbiani, Massimiliano; Muscatello, Antonio; Perseghin, Paolo; Bani, Marco; Incontri, Arianna; Squillace, Nicola; Lapadula, Giuseppe; Gori, Andrea; Bandera, Alessandra
Abstract : Background: The contribution of monocyte activation in the development of HIV-associated neurocognitive disorders is not completely understood. This study aimed to explore the predictive value of peripheral monocyte/macrophage (M/M) phenotypes on the evolution of cognitive performance in a population of virologically suppressed HIV-infected patients. Setting: Prospective, observational, longitudinal study. Methods: HIV-1-infected patients with HIV-RNA <50copies/mL for >12 months underwent neuropsychological examination at baseline and after 1 year. Cognitive performance was evaluated using Z-transformed scores, and neurocognitive impairment (NCI) was defined according to Frascati criteria. Peripheral M/M phenotypes (classic CD14 ++ CD16 −, intermediate CD14 ++ CD16 +, and nonclassic CD14 + CD16 ++ ) and specific surface activation markers (eg, CD163, CD11b, and CD38) were evaluated using flow cytometry at baseline. Predictive value of peripheral M/M phenotypes on the evolution of cognitive performance over 1-year follow-up was also evaluated. Results: Overall, 54 patients [85.2% men, median age 50 years (range 27–60 years), 27.8% hepatitis C virus coinfected, 48.1% with past AIDS-defining events, median nadir CD4 83 cells/μL (range 1–334), median baseline CD4 547 cells/μL (range 136–1652)] were enrolled. Proportion of patients with NCI was low, accounting for 13% at baseline and 16.5% after 1 year ( P = 0.687). Memory was the only single domain in which decreased performance after 1 year was observed (−0.25 Z-score, P = 0.025). In patients with significant decrease (≥0.5 SD) in memory performance (n = 20), significantly lower CD14 ++ CD16 + CD163 + (% CD14 ++ CD16 + ) ( P = 0.038) and higher CD14 + CD38 + (% CD14 + ) ( P = 0.030) levels were observed. Conclusions: In virologically suppressed HIV-infected patients, the evolution of memory performance could be linked to the expression of certain peripheral activated M/M phenotypes. Such associations should be verified in larger populations over the long term. Abstract : Supplemental Digital Content is Available in the Text.